Three cars leave for in equal time intervals. They reach simultaneously and then leave for point which is from . The first car arrived there ( at ) an hour after the second car, and third car, having reached , immediately reverses the direction and form meets the first car. Find the speed of the first car (in ).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can say that the distance between B and C is:
V c a r 2 × t = 1 2 0
V c a r 1 × ( t + 1 ) = 1 2 0
( t refers to the time it took for car2 to get from B to C )
We need to experss V c a r 2 in proportion to V c a r 1 to solve these two equations.
The time it took for car3 to drive 120 km from B to C + 40 km back Is equal to The time it took for car1 to drive 80 km from B in the direction of C :
V c a r 1 8 0 = V c a r 3 1 2 0 + 4 0
8 0 × V c a r 3 = 1 6 0 × V c a r 1
V c a r 3 = 2 × V c a r 1
We can see that V c a r 3 is twice as big as V c a r 1 .
Since we know that the time intervals of the cars leaving from A to B are equal, and that the cars reach B simultaneously we can write:
A B = V c a r 1 × T = V c a r 3 × ( T − 0 . 5 T ) = V c a r 2 × ( T − x T )
( T refers to the time it took for car1 to get from A to B )
It took car3 only half the time it took car1 to get from A to B because it had twice the speed.
( T − x T ) which is the time interval of car2 (faster than car1 ) has to be 2 times smaller than the interval of car3 ( T − 0 . 5 T ) in order for the time intervals between the 3 cars to be equal (equal to 0 . 2 5 T ).
(Equal interavals between the cars can be: 0 . 2 5 T in that case V c a r 3 > V c a r 2 , or 0 . 5 T which makes : ( T − x T ) = T − 1 T = 0 in other words - not possible ).
( T − x T ) = 2 ( T − 0 . 5 T )
T − x T = − 0 . 2 5 T
x = 0 . 2 5
From substituting x we can get the connection we wanted between V c a r 1 and V c a r 2 :
V c a r 1 × T = V c a r 2 × ( T − 0 . 2 5 T )
V c a r 1 = 0 . 7 5 × V c a r 2
V c a r 2 = 0 . 7 5 V c a r 1
Then we go back to our first two equations and replace V c a r 2 :
0 . 7 5 V c a r 1 × t = 1 2 0
V c a r 1 × ( t + 1 ) = 1 2 0
And now we solve for V c a r 1 :
t = V c a r 1 9 0
V c a r 1 × ( V c a r 1 9 0 + 1 ) = 1 2 0
9 0 + V c a r 1 = 1 2 0
V c a r 1 = 3 0 km/hr